Indices of Bad Governance by African Political Leaders: The Case Study of Central African Republic, Democratic Republic of the Congo and Uganda - Blaise Ngambinzoni Kombeto; Romain Bakola Dzango; Modeste Ndaba Modeawi; Gédéon Bongo Ngiala; Muhammad Ridwan; Koto-te-Nyiwa Ngbolua (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Marcel SONY LabouTansi, the author of the novel "The Shameful State", denounces the dictatorial system often practiced by most African leaders in the management of the "res publica". He paints the barbarity of man in relation to his fellow man. It also presents the duality between the traditional society characterized by democracy, peace ... and the modern society based on dictatorship in which the government behaves as a state, as absolute master, and the governed in the eternal "- mute", "voiceless". It invites the recipients to renounce to the bad principle in order to establish democracy, a system that respects the individual freedom of the people, that of human rights, of professional promotion for the harmonious development of a sovereign and democratic State. The novel "The Shameful State" unfolds the spiral of the unpleasant reign of a megalomaniacal, criminal and lustful president, Colonel Martillimi Lopez, who "shamefully" manages power and ends with the crying and gnashing of his constituents' teeth. After having committed: pedophilia, adultery, assassination of opponents, he was deposed by his relatives who created an insurrection and was forced to hand over power to civilians to return to his native village.